1989
DOI: 10.1038/clpt.1989.68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coadministration on the pharmacokinetics of mezlocillin and cefotaxime in healthy volunteers and in patients with renal failure

Abstract: The pharmacokinetic disposition of cefotaxime, desacetyl cefotaxime, and mezlocillin after the administration of each drug singly and in combination was examined in eight healthy volunteers and in five anuric patients with end-stage renal disease (ESRD). In the presence of ESRD, the total body clearance of cefotaxime decreased from 256.7 +/- 41.5 to 65.4 +/- 42.0 ml/min, and its elimination half-life (t1/2) increased from 1.1 to 3.6 hours as compared with healthy volunteers. Concomitant administration of mezlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Concomitant administration of mezlocillin with cefotaxime in eight healthy volunteers and five patients with end-stage renal disease (ESRD) suggested that the lower cefotaxime doses may prove to be adequate in patients with normal renal function with co-administered mezlocillin [341]. Although the mechanism of this nonrenal PK interaction is still unclear, the authors suspected the character of the interaction to be of metabolic origin [341].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant administration of mezlocillin with cefotaxime in eight healthy volunteers and five patients with end-stage renal disease (ESRD) suggested that the lower cefotaxime doses may prove to be adequate in patients with normal renal function with co-administered mezlocillin [341]. Although the mechanism of this nonrenal PK interaction is still unclear, the authors suspected the character of the interaction to be of metabolic origin [341].…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism of this nonrenal PK interaction is still unclear, the authors suspected the character of the interaction to be of metabolic origin [341]. …”
Section: Resultsmentioning
confidence: 99%
“…The PK parameters of a series of 20 cephalosporins were collected from the literature,11–32 and compounds were divided into working (training and testing) and validation subsets (Table 1). Data for all compounds were taken from studies using intravenous administration of the drug, with the exception of cefaclor.…”
Section: Methodsmentioning
confidence: 99%
“…This has been frequently shown with β‐lactams and probenecid, a well‐known inhibitor of tubular secretion [9, 12, 13]. Renal interactions have also been reported when two β‐lactams were given together [14–17]. Therefore, the possibility of PK drug–drug interactions should be considered when two or more β‐lactams are given in combination.…”
Section: Introductionmentioning
confidence: 98%